Effect of Sanitizer on obliteration of SARS –CoV2/COVID 19: A mini review. (2022) - Andal, V.; Lakshmipathy, R.; Jose, Deepa
Abstract: Corona virus is a respiratory virus which causes infectious Covid-19 (Corona Virus −2019) disease and globally the virus continues to pose major risks of mortality. It is lucid that close links are the key aspect for transitory of communicable Corona virus. Rapid research is in progress to identify prolific drugs and vaccine for Covid-19 however, it is a time consuming process. Social distancing and Sanitizers are helpful in combating virus and safeguarding the human health. Hand sanitizers are prolific when hands washing with soaps are not possible. Sanitizers are effective antibacterial agents and classified into two types as alcohol based and alcohol free. Among which alcohol based sanitizers are prospective in persuading the public needs. Efficient use of alcohol-based sanitizers during this epidemic season could significantly reduce the propagation of corona virus. This review aims at explaining the interactions of virus with hand sanitizers.